The role of metadata and XMP in Digital Asset Management 2 - Earley, Seth (Henry Stewart Talks, 2010)
Semantics, information architecture and metadata, Information versus semantic architecture, Multiple uses for metadata and taxonomy, Taxonomy, metadata and asset management, Taxonomy definition, Defining metadata, Content object models, What is a content model?, Metadata for a product page, How metadata allows various views of content, Content assembly, How content metadata allows reuse, Deriving a content model, Use case, management of marketing assets, Navigating with "facets", "Facet" is a top level category in the taxonomy, Visualize result sets as parameter groupings, The possible combinations of navigational paths, Leveraging metadata across the value chain, Searching, browsing, finding, extending, Changing consumer marketplace, Digital, content and asset management, Content value chain, The User Experience (UX), Metadata and search, Explicit metadata versus implicit metadata, Search index points to document, Examples of implicit metadata, Types of term relationships, Associative relationships, Faceted search, Is it search or navigation?, Taxonomy as facets, DAM taxonomy framework, Detailed definitions of art techniques, Detailed definitions of art styles, Tagging, Digital asset management drivers, A simple user experience & metadata, How systems leverage taxonomy differently